Новый вид рода Paraphlegopteryx (Trichoptera, Lepidostomatidae) из Индии - Parey, S.H.; Singh Saini, M. (Вестник зоологии, 2012)
Новый вид рода Paraphlegopteryx Ulmer описан из Индийских Гималаев, а именно Paraphlegopteryx weaveri Parey et Saini, sp. n. относящийся к группе P. composite, из поселения Земитханг (штат Аруначал-Прадеш). В дополнении к этому роду представлены 15 видов из Индии. Приведена таблица для определения всех 15 видов (модификация Вивера (1999). A new species of genus Paraphlegopteryx Ulmer is described and presented from Indian Himalaya, namely Paraphlegopteryx weaveri Parey et Saini, sp. n. from Zemithang (Arunachal Pradesh) belonging to the P. composite group. As an addition to this genus the 15 valid species from India is represented. A key to all the 15 species of India which is modified after Weaver (1999) is provided.